Jawabanmu

2014-09-06T20:13:28+07:00
A) 10p - 5q - (-25p + 9q) = 10p - 5q + 25p - 9q = 35p - 14q
b) -8x²y - 36 xy - (-7xy - 14x) = -8x²y - 36xy +7xy + 14x = =8x²y - 29xy + 14x

7x - 6y + 8 + (-3x+11y-4) = 7x - 6y + 8 - 3x+11y - 4 = 4x + 5y + 4
2014-09-06T20:15:03+07:00
A. (-25p+9q) dari (10p-5q) = (10p - 5p) - (-25p + 9q) = 10p - 5q + 25p - 9p = 35p - 14q
B . -7x(y+2) dari -4xy(2x+9) = -4xy (2x+9) - (-7x) (y+2) = -8ײy - 9×y - -7xy + - 14× = -8x²y - 2xy - 14 x
C. (7x -6y+8) dan (-3x+11y-4) = 7x -6y + 8 + -3x + 11y - 4 = 4x + 5y + 4
A. (-25p+9q) dari (10p-5q) = (10p - 5p) - (-25p + 9q) = 10p - 5q + 25p - 9p = 35p - 14q
B . -7x(y+2) dari -4xy(2x+9) = -4xy (2x+9) - (-7x) (y+2) = -8ײy - 9×y - -7xy + - 14× = -8x²y - 2xy - 14 x
C. (7x -6y+8) dan (-3x+11y-4) = 7x -6y + 8 + -3x + 11y - 4 = 4x + 5y + 4